2014
DOI: 10.1159/000366437
|View full text |Cite
|
Sign up to set email alerts
|

Can Steroids plus Surgery Become a First-Line Treatment of Idiopathic Granulomatous Mastitis?

Abstract: Background: The aim of this study is to compare the clinical course of idiopathic granulomatous mastitis (IGM) treated with low-dose oral corticosteroid therapy alone as opposed to treatment with low-dose corticosteroid therapy followed by surgery. Patients and Methods: 37 patients were treated with an approach that consisted of methylprednisolone at a dose of 0.5 mg/kg/day followed by wide excision, and 23 patients were treated with an approach that consisted only of methylprednisolone. The treatment efficacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 25 publications
1
41
0
Order By: Relevance
“…The characteristic of reviewed articles is summarized in Table (). The total number of articles was 70, 59 in group A and 11 in group B.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristic of reviewed articles is summarized in Table (). The total number of articles was 70, 59 in group A and 11 in group B.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristic of reviewed articles is summarized in Table 1( [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]…”
Section: Re Sultsmentioning
confidence: 99%
“…Recurrence may be observed despite broad surgical excision in IGM. The IGM recurrence rate varies between 5% and 50% according to the literature . Post‐excision recurrence may be as high as 50% .…”
Section: Introductionmentioning
confidence: 99%
“…There is an ongoing debate in the literature whether IGM is a surgical disease or not (6,7,10,11). The majority of the publications on the subject originate from Mediterranean countries (Turkey, Egypt) as well as countries from the Middle East (1,2,6,10,12,13).…”
Section: Case Presentationmentioning
confidence: 99%
“…It is commonplace among relevant literature that conservative (medical) treatment is correlated with increased rates of disease response or resolution (around 75%) but also high early disease recurrence (around 30%) (16). Around 40% of the patients under steroids develop side effects, recurrence or persistence of symptoms under steroid treatment and mandate immunosuppressive treatment (6,10,16). On the contrary, studies that included surgical resection as a firstline treatment demonstrated significantly superior results compared to steroid-alone treatment in terms of recurrence and post-treatment recovery (6 months in conservative vs. 1 month in surgery; P<0.009) (6,10).…”
Section: Case Presentationmentioning
confidence: 99%